Rel Is Required for Morphogenesis of Resting Cells in Mycobacterium smegmatis - Wu, Mu-Lu; Chan, Chuu Ling; Dick, Thomas (Frontiers in Microbiology, 2016)
Recently we showed that upon transfer of growing Mycobacterium smegmatis into saline, the bacilli exited the canonical cell division cycle and formed septated multi-nucleoided cells. Under shock starvation (i.e. in saline without any carbon source), differentiation terminated at this stage with internally remodeled Large Resting Cells, LARCs. Whereas under gentle starvation (i.e. in saline with trace amounts of a carbon source), the septated multi-nucleoided bacilli completed cell division and separated into mono-nucleoided Small Resting Cells, SMRCs. This demonstrated that the non-sporulating mycobacteria are in fact capable of forming morphologically differentiated resting cells when exposed to starvation. Depending on the specific starvation conditions they can form two different resting cell types, LARCs or SMRCs, which share a common cellular differentiation pathway. The mRNA encoding the (p)ppGpp synthetase Rel was found to be transiently upregulated immediately upon starvation under both conditions, suggesting a role for the stringent response factor in both LARC and SMRC development. Here, we disrupted Rel function by generating two types of mutant M. smegmatis strains: a rel nonsense mutant (relE4TAG) in which translation is prematurely terminated at codon 4, and a rel deletion mutant (△rel) in which the entire coding sequence was deleted. Both mutants showed identical phenotypes: sparse septum formation, less DNA compaction and failure in formation of both the septated multi-nucleoided LARCs and the small-cell morphotype SMRC under starvation conditions. All phenotypes were rescued through the introduction of a wild-type copy of rel. Therefore, we conclude that loss-of-function mutations in rel block the development of both LARCs and SMRCs by preventing the first morphogenetic step in mycobacterial resting cell development, the formation of septated multi-nucleoided cells. Interestingly, in contrast to Rel’s role in most other bacteria, starvation survival was not affected by loss of rel function. Our results suggest that Rel may play a starvation-induced morphogenetic role in mycobacteria.